2015
DOI: 10.1590/0104-1169.0078.2595
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for cardiovascular diseases and the coverage by the family health strategy

Abstract: Objective: to verify the correlation between the rates of hospitalization for primary care-sensitive cardiovascular diseases and the coverage by the Family Health Strategy of residents of the State of Paraná, by regional health divisions, from 2000 to 2011. Method: ecological study developed from data of the Hospital Information System of the Brazilian Unified Health System (SUS) and the Department of Primary Care of the Ministry of Health. The rates of hospitalization for cardiovascular diseases were correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
6
0
10
Order By: Relevance
“…This information related to the costs of hospitalizations are usually obtained by DATASUS, a database where there is a high quantity of hospitalizations for CVDs, exceeding the average for other types of diseases and thus alerting SUS managers to develop health indicators to enable adoption of measures to reduce them [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This information related to the costs of hospitalizations are usually obtained by DATASUS, a database where there is a high quantity of hospitalizations for CVDs, exceeding the average for other types of diseases and thus alerting SUS managers to develop health indicators to enable adoption of measures to reduce them [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Embora os diferentes trabalhos tenham apontado resultados semelhantes, ou seja, um decréscimo dessas internações coincidente com a maior cobertura da ESF, suas conclusões divergiram. Para Lentsck e Mathias, 14 o aumento da cobertura populacional pela ESF pode ter sido um fator importante para a diminuição das ICSAP cardiovasculares de sua população. Já Batista et al 15 trouxeram uma discussão interessante, após observarem que municípios próximos à capital e da região metropolitana apresentaram maiores taxas de internação, enquanto os de piores condições socioeconômicas, a menor taxa média.…”
Section: Resultado E Discussãounclassified
“…Em síntese, houve uma distribuição igualitária dos estudos selecionados para esta revisão quanto às suas conclusões. Dos 20 trabalhos (n=20), 10 (n=10; 50,0%) concluíram que houve correlação inversa entre a cobertura da ESF e as taxas de ICSAP, ou seja, uma maior cobertura desta estratégia da atenção primária ou o acompanhamento regular pela ESF resultou em menores coeficientes por essas internações 3,5,7,11,13,14,17,20,22,23 , enquanto outros 10 trabalhos (n=10; 50,0%) não encontram a mesma relação ou essa relação não foi significativa. 2,4,8,12,15,16,18,19,21,24…”
Section: Resultado E Discussãounclassified
“…The authors attribute this reduction to PHC's expansion, covering more than 60% of the population, improving access to healthcare and the significant reduction for prevalence of smoking in Brazil, from 34.8% (1989) to 8.7% (2014). 1,3 But in our study region it is necessary to be attentive, a survey that assessed rates of hospitalization for cardiovascular disease sensitive to PHC and coverage of the FHS for residents in the State of Paraná, showed that in our region there was no significant reduction of hospitalizations, revealing little stability or falls in these rates, 26 indicating that even with greater coverage by the FHS there are still no improvements in the indicators, being needed a better performance of the nursing team and other health professionals with setting targets based on the Strategic Action Plan for Confronting the CNTD. 2 And further studies in order to identify likely factors and causes that have influenced the results, such as access and quality of service.…”
mentioning
confidence: 77%